Serious games : developing the Philippines-Spanish era as a strategy role playing game using flash - JOHN ARIEL, SALVADORA (Archīum Ateneo, 2012)
Role playing games have the power of immersing players in huge, extensive worlds. In RPGs, past environments can be recreated and experienced by players who were not present in that time frame. RPG worlds give players a glimpse of life in these worlds tha